Acid and alkali resistant separation membrane as well as preparation method and application thereof
By using acid- and alkali-resistant separation membranes in salt lake brine, the problems of low separation efficiency and poor acid resistance of magnesium lithium are solved, and efficient separation of magnesium lithium and long-life membrane performance are achieved.
Patent Information
- Application Number
- CN202311014364.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-08-11
AI Technical Summary
The prior art has problems of low separation efficiency and poor acid resistance in the magnesium lithium separation process in the salt lake brine, resulting in poor separation effect of magnesium lithium.
An acid-base-resistant separation membrane is adopted, which consists of a base material layer, a porous support layer, a poly(triazine-urea) layer and a modified layer. The modified layer contains a crosslinked polymer, and is passed through polyphenol and the first poly The self-assembly reaction of amines is formed, which improves the density and acid-base tolerance of the membrane.
The separation membrane maintains high water flux in an acid/alkali environment, and has a high magnesium-lithium separation coefficient, which significantly improves the magnesium-lithium separation efficiency and extends the service life of the membrane.
Smart Images

Figure CN119455701A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the membrane field, and in particular to an acid-base resistant separation membrane and a preparation method and application thereof. Background Art
[0002] As a new energy and strategic resource, lithium resources are widely used in lithium batteries, aerospace, pharmaceutical industry, glass and ceramic industry. In recent years, with the rapid development of new energy vehicles, the demand for lithium as a core raw material has also increased year by year. Salt lake lithium resources account for about 70% of the world's lithium reserves. Compared with mining lithium ore, extracting lithium from brine has large reserves, low cost and simple process, which has become the development trend of the global lithium extraction industry. Usually, the lithium resources in salt lake brine exist in the form of lithium chloride, but there is often a large amount of magnesium chloride coexisting with it. The radius of lithium ions (7.4×10 -13 m) is very close to magnesium ion (7.2×10 -13 m), and lithium ions and magnesium ions have similar chemical properties and are difficult to separate, which poses great difficulties in extracting lithium from salt lake brine. my country's salt lake brine has a high magnesium-to-lithium ratio. Effective separation of magnesium ions and lithium ions in brine resources is the key to the development of my country's salt lake lithium resources.
[0003] Generally, the specific process of lithium extraction from salt lakes is "one lake, one policy", and the conditions of the brine determine the corresponding lithium extraction technology routes. The precipitation method is to concentrate the salt lake brine, then use acidification or extraction methods to remove impurity ions, and then add Na 2 CO 3 Li precipitation 2 CO 3 process. This process is cumbersome, energy-intensive, and is not suitable for domestic brines with high magnesium-to-lithium ratios. The solvent extraction method uses the difference in solubility of magnesium ions and lithium ions in the extractant to separate the two. The extractant is relatively expensive and corrosive to equipment. The extraction of lithium by calcination will be accompanied by the production of a large amount of hydrogen chloride gas, which will cause corrosion to the equipment and energy consumption problems. Taking into account the technical feasibility and economic benefits, the adsorption-membrane lithium extraction process has become the mainstream choice for my country's high magnesium-to-lithium ratio salt lakes, contributing 93% of my country's salt lake lithium production capacity in 2020.
[0004] Specifically, the adsorption-membrane lithium extraction process uses a selective adsorbent to adsorb lithium ions and a small amount of other ions, then desorbs the adsorbent, and then uses a nanofiltration membrane to filter the desorbed liquid to further separate lithium ions and other ions, and concentrate the filtrate to finally precipitate industrial-grade lithium carbonate. The problem is that the desorption process of the adsorbent needs to be carried out under acidic conditions, which makes the original solution of the nanofiltration process acidic. However, the commercial nanofiltration membrane material is mainly polyamide, and under acidic conditions, the C=O bond is easily affected by H +The nucleophilic electrons attack the amide bond, causing hydrolysis of the amide bond, which destroys the structure of the membrane separation layer and reduces the interception performance. In addition, commercial nanofiltration membranes have problems such as low magnesium-lithium separation efficiency and short service life. It is urgent to develop nanofiltration membranes with positively charged surfaces, good acid resistance and high magnesium-lithium separation efficiency to meet the application scenario requirements of magnesium-lithium separation. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of low magnesium-lithium separation efficiency and poor acid and alkali resistance in the prior art, and to provide an acid-alkali resistant separation membrane and its preparation method and application. The poly(triazine amine-urea) has inert chemical groups, so that the acid-alkali resistant separation membrane has high acid / alkali tolerance; the modification layer includes a cross-linked polymer, so that the acid-alkali resistant separation membrane has a high density and a high surface electrode potential (Zeta potential). When it is used for magnesium-lithium separation, it can maintain a high water flux and have a high magnesium-lithium separation coefficient, and can be used in the field of water treatment separation.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides an acid-base resistant separation membrane, wherein the separation layer comprises a substrate layer, a porous support layer, a poly(triazineamine-urea) layer and a modification layer in sequence;
[0007] The cross-linked polymer forming the modified layer includes structural units provided by polyphenols and structural units provided by the first polyamine, and at least part of the structural units provided by the polyphenols are also connected to the poly(triazineamine-urea) layer via the ortho position of the phenolic hydroxyl group;
[0008] The pore size of the separation membrane is 0.1-0.5 nm, and the surface Zeta potential of the separation membrane is 0-30 mV.
[0009] The second aspect of the present invention provides a method for preparing an acid-base resistant separation membrane, wherein the preparation method comprises the following steps: sequentially preparing a porous support layer, a poly(triazineamine-urea) layer and a modification layer on a substrate layer;
[0010] Among them, the method for preparing the modified layer includes: under a first pressure, while the polyphenol solution is kept flowing, a poly(triazineamine-urea) layer side of a material including a substrate layer, a porous support layer, and a poly(triazineamine-urea) layer is brought into first contact with a polyphenol solution; under a second pressure, while the first polyamine solution is kept flowing, a poly(triazineamine-urea) layer side of the material is brought into second contact with a first polyamine solution to complete a self-assembly reaction.
[0011] The third aspect of the present invention provides an acid-base resistant separation membrane prepared by the above preparation method.
[0012] The fourth aspect of the present invention provides the application of the above acid-base resistant separation membrane in the field of water treatment.
[0013] Through the above technical solution, the separation membrane provided by the present invention and its preparation method and application have the following beneficial effects:
[0014] The poly(triazineamine-urea) layer in the separation membrane provided by the present invention improves the acid-base tolerance of the separation membrane, so that it can also be used for magnesium-lithium separation in an acid / alkaline environment; the modified layer includes a cross-linked polymer, so that the separation membrane has a smaller pore size and improves the density of the separation membrane; the higher positive charge density in the cross-linked polymer enables the separation membrane to maintain a high water flux, and at the same time the separation membrane has a high magnesium-lithium separation coefficient, and can be used in the field of water treatment separation.
[0015] The present invention provides a method for preparing a separation membrane. The polyphenol and the first polyamine can undergo Michael addition reaction on the surface of a poly(triazineamine-urea) layer to form a cross-linked structure. The structural units provided by some of the polyphenols are also connected to the poly(triazineamine-urea) layer through the carbon atoms at the ortho position of the phenolic hydroxyl group, making the stacking more compact. The poly(triazineamine-urea) layer makes the separation membrane acid / alkali tolerant. The cross-linked polymer in the modified layer improves the density of the separation membrane and the positive charge density on the surface of the separation membrane, so that the separation membrane has a higher magnesium-lithium separation coefficient while maintaining a higher water flux. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the XPS N atomic spectrum of the surface of the acid-base resistant separation membrane N1 prepared in Example 1. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] The first aspect of the present invention provides an acid-base resistant separation membrane, wherein the separation layer comprises a substrate layer, a porous support layer, a poly(triazineamine-urea) layer and a modification layer in sequence;
[0019] The cross-linked polymer forming the modified layer includes structural units provided by polyphenols and structural units provided by the first polyamine, and at least part of the structural units provided by the polyphenols are also connected to the poly(triazineamine-urea) layer via the ortho position of the phenolic hydroxyl group;
[0020] The pore size of the separation membrane is 0.1-0.5 nm, and the surface Zeta potential of the separation membrane is 0-30 mV.
[0021] The inventors of the present invention have found in their research that the acid-base resistant separation membrane includes the layers described above, which can make the separation membrane have the pore size range described in the present invention, and make the separation membrane have the surface Zeta potential range described in the present invention, indicating that the separation membrane has high density and high surface Zeta electrode potential. When it is used for magnesium-lithium separation in an acid / base environment, it can exclude divalent magnesium ions while allowing monovalent lithium ions to pass as much as possible, and has a high magnesium-lithium separation coefficient. At the same time, the synergistic cooperation of several membrane layers makes the separation membrane have a higher water flux. When it is used in the field of water treatment, it can allow more flow to pass through and improve the treatment efficiency.
[0022] In the present invention, the pore size of the acid-base resistant separation membrane is measured by the polyethylene glycol (PEG) solute transfer method, and the detailed steps are as follows:
[0023] (1) Test the retention rate of separation membrane for PEG with different molecular sizes;
[0024] (2) Linear fitting was performed between PEG size and retention rate in a logarithmic-probability coordinate system, and the PEG size corresponding to 50% retention rate was the average pore size of the separation membrane.
[0025] In the present invention, the surface Zeta potential of the acid-base resistant separation membrane is measured by a potential analyzer.
[0026] Furthermore, the pore size of the acid- and alkali-resistant separation membrane is 0.15-0.3 nm, and the surface Zeta potential of the separation membrane is 5 mV to 20 mV.
[0027] According to the present invention, the modified layer includes a structural unit shown in Formula I;
[0028]
[0029] In the present invention, the inventors have found through research that when the nitrogen element in the modified layer of the separation membrane is tested by XPS, the modified layer of the acid-base resistant separation membrane provided by the present invention contains the structural unit shown in Formula I, that is, there is a π-π structure formed by benzene ring-nitrogen atom-benzene ring in the modified layer. * The electronic conjugated structural unit further indicates that at least part of the structural units derived from the polyphenol in the modified layer undergo cross-linking reaction with the structural units derived from the first polyamine and / or the nitrogen atoms from the poly(triazineamine-urea) layer through the ortho position of the phenolic hydroxyl group, so that the pore size of the acid-base resistant separation membrane comprising the modified layer is further reduced, and the density of the acid-base resistant separation membrane is further improved, thereby improving the magnesium-lithium separation efficiency when the acid-base resistant separation membrane is used for magnesium-lithium separation.
[0030] According to the present invention, the content of the structural units provided by the polyphenol on the film surface is 2×10 -3 -5×10 -2mg / cm 2 The content of the structural unit provided by the first polyamine on the membrane surface is 1×10 -3 -2.5×10 -2 mg / cm 2 .
[0031] In the present invention, in the separation membrane, the content of the structural unit provided by the polyphenol and the structural unit provided by the first polyamine on the membrane surface of the acid-base resistant separation membrane is measured according to the following steps:
[0032] The membrane including the substrate layer, the porous support layer, and the poly(triazineamine-urea) layer was dried in a vacuum oven at 60°C for 24 hours, and the mass of the membrane was weighed as M. n , mg; the membrane is loaded into the membrane pool, and the feed tank is a certain concentration of polyphenol aqueous solution. After circulating for a certain period of time under certain conditions, the membrane is taken out, the surface of the membrane is rinsed with deionized water, and then dried at 60°C for 24 hours. The mass of the membrane is weighed as W n , mg; then the membrane is loaded into the membrane pool, and the feed tank is a first polyamine aqueous solution of a certain concentration. After circulating for a certain period of time under certain conditions, the membrane is taken out, the membrane surface is rinsed with deionized water, and then dried at 60°C for 24 hours. The mass of the membrane is weighed as N n , mg; the content of polyphenols on the membrane surface after each modification of the separation membrane P n And the content of polyamine T n They are calculated by the following formulas:
[0033]
[0034] When n is greater than 1, M n =N n-1 ; When n = 1, M n That is the mass of the original poly(triazineamine-urea) membrane;
[0035]
[0036] After the separation membrane is self-assembled, the total content of the polyphenol on the surface is ΣPn, n≥1, and the total content of the first polyamine on the surface is ΣTn, n≥1;
[0037] Where n is the number of self-assembly times and S is the effective membrane area in cm 2 .
[0038] In the present invention, the inventors have found through research that when the content of the structural units provided by the polyphenol and the structural units provided by the first polyamine on the membrane surface meets the above range, the separation membrane has a suitable density and thickness, thereby ensuring that the acid-base resistant separation membrane has a higher magnesium-lithium separation coefficient and water flux.
[0039] Furthermore, the content of the structural units provided by the polyphenol on the membrane surface is 1×10 -2 -3×10 -2 mg / cm 2 The content of the structural units provided by the first polyamine on the membrane surface is 5×10 -3 -2×10 -2 mg / cm 2 .
[0040] According to the present invention, the content of N atoms in the modified layer is 10-20 at.%.
[0041] In the present invention, the content of N atoms in the modified layer is measured by an X-ray photoelectron spectroscopy analyzer.
[0042] In the present invention, when the content of N atoms in the modified layer satisfies the above range, the separation membrane can have a high surface electrode potential and excellent hydrophilicity, and when used for magnesium-lithium separation, it has a high magnesium-lithium separation efficiency and a high water flux.
[0043] Furthermore, the content of N atoms in the modified layer is 14-18 at.%.
[0044] According to the present invention, the contact angle of the separation membrane is 20-60°.
[0045] In the present invention, the contact angle of the separation membrane is measured according to the following method: the surface contact angle of the composite membrane sample is tested by the sessile drop method using a DSA100 surface contact angle meter produced by KRUSS, Germany. Before the test, the sample is dried in a vacuum oven at 60°C for 30 minutes to remove surface and internal moisture, and then the dried membrane is attached to a flat glass slide with double-sided tape. The volume of each water droplet during the test is 2 μL. The water droplet is tested immediately after being dropped on the membrane surface for 3 seconds. The final contact angle is determined by taking the average value after multiple measurements.
[0046] In the present invention, the separation membrane has a contact angle within the range of the present invention, which indicates that the separation membrane has excellent hydrophilicity and can enable the separation membrane to have excellent water flux.
[0047] Furthermore, the contact angle of the separation membrane is 20-50°.
[0048] According to the present invention, the separation membrane has a thickness of 100-200 μm.
[0049] According to the present invention, the thickness of the substrate layer is 30-150 μm, preferably 50-120 μm.
[0050] According to the present invention, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm.
[0051] According to the present invention, the thickness of the poly(triazineamine-urea) layer is 10-500 nm, preferably 50-200 nm.
[0052] According to the present invention, the thickness of the modified layer is 10-200 nm, preferably 10-60 nm.
[0053] In the present invention, the thickness of the separation membrane, the porous support layer, and the poly(triazineamine-urea) layer are measured by a spiral micrometer and a scanning electron microscope, and the thickness of the modified layer is obtained by subtracting the thickness of the substrate layer, the porous support layer, and the poly(triazineamine-urea) layer from the thickness of the separation membrane. The thickness of the substrate layer is the thickness measured before coating the porous support layer material solution.
[0054] The inventors of the present invention have found in their research that when the thickness ranges of the above-mentioned layers are met, the above-mentioned layers can cooperate better, so that the separation membrane has a small pore size and a high Zeta potential. When it is used for magnesium-lithium separation in an acidic or alkaline environment, it can take into account both higher magnesium-lithium separation efficiency and water flux.
[0055] According to the present invention, the material of the substrate layer is not particularly limited, and can be a material commonly used in the art that has a certain strength and is suitable for nanofiltration or reverse osmosis and can play a supporting role. However, preferably, the material of the substrate layer is selected from polyester non-woven fabric and / or polyethylene non-woven fabric.
[0056] According to the present invention, the poly(triazineamine-urea) layer is synthesized from a second polyamine, a triazine compound containing at least two C-Cl bonds and polyisocyanate.
[0057] In the present invention, the poly(triazineamine-urea) layer as described above has inert chemical groups, so that the acid-base resistant separation membrane finally prepared can adapt to the acid / base environment and has a suitable cross-linked structure, and the amino groups therein can better retain divalent magnesium ions.
[0058] Furthermore, the second polyamine is selected from at least one of triethylenetetramine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine, preferably polyethyleneimine and / or polyethylenepolyamine.
[0059] Furthermore, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine, preferably cyanuric chloride.
[0060] Further, the polyisocyanate is selected from at least one of meta-xylylene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate and 1,4-cyclohexyl diisocyanate, preferably 1,3-phenylene diisocyanate.
[0061] According to the present invention, the modified layer is obtained by self-assembly reaction of polyphenol and first polyamine on the poly(triazineamine-urea) layer.
[0062] According to the present invention, the polyphenol is selected from at least one of tannic acid, tea polyphenols, lignin, sodium lignin sulfonate, apple polyphenols, grape polyphenols, eriodictyol, naringenin, epicatechin, luteolin, gallic acid, protocatechuic acid, apigenin, kaempferol, myricetin and genistein, preferably tannic acid and / or tea polyphenols.
[0063] According to the present invention, the first polyamine is selected from at least one of polyethyleneimine, polyethyleneamine, polyethylenepolyamine, tetraethylenepentamine, triethylenetetramine, diethylenetriamine, polyethylenepolyamine, piperazine and N-aminoethylpiperazine, preferably at least one of polyethyleneimine, tetraethylenepentamine, triethylenetetramine and polyethylenepolyamine.
[0064] The second aspect of the present invention provides a method for preparing an acid-base resistant separation membrane, wherein the preparation method comprises the following steps: sequentially preparing a porous support layer, a poly(triazineamine-urea) layer and a modification layer on a substrate layer;
[0065] Among them, the method for preparing the modified layer includes: under a first pressure, while the polyphenol solution is kept flowing, a poly(triazineamine-urea) layer side of a material including a substrate layer, a porous support layer, and a poly(triazineamine-urea) layer is brought into first contact with a polyphenol solution; under a second pressure, while the first polyamine solution is kept flowing, a poly(triazineamine-urea) layer side of the material is brought into second contact with a first polyamine solution to complete a self-assembly reaction.
[0066] According to the present invention, the first pressure and the second pressure are each independently 1-3 MPa.
[0067] In the present invention, when the pressure applied during the preparation of the modified layer is controlled to meet the above range, it can ensure that the prepared acid-base resistant separation membrane has a higher density, and at the same time, the content of the structural unit provided by the first polyamine in the separation membrane is higher, so that the separation membrane has higher hydrophilicity, and finally the separation membrane has excellent magnesium-lithium separation performance and water permeability.
[0068] Furthermore, the first pressure and the second pressure are each independently 1.5-2 MPa.
[0069] According to the present invention, the amounts of the polyphenol solution and the first polyamine solution are such that the mass ratio of the polyphenol to the first polyamine is 0.1-10:1.
[0070] In the present invention, when the mass ratio of the polyphenol to the first polyamine is controlled to meet the above range, in addition to ensuring that the polyphenol and the polyamine can fully react and ensuring that the prepared separation membrane has the pore size required by the present invention, it can also ensure that the surface of the separation membrane contains more residual amino groups, so that the acid-base resistant separation membrane has the high surface Zeta potential and hydrophilicity required by the present invention. When the acid-base resistant separation membrane is used for magnesium-lithium separation, the acid-base resistant separation membrane has a higher divalent magnesium ion retention rate and water flux.
[0071] Furthermore, the amounts of the polyphenol solution and the first polyamine solution are such that the mass ratio of the polyphenol to the first polyamine is 0.25-6:1.
[0072] According to the present invention, the concentration of the polyphenol is 0.00001 wt %-1 wt %.
[0073] According to the present invention, the concentration of the first polyamine is 0.00001 wt %-1 wt %.
[0074] In the present invention, the concentrations of the polyphenol solution and the first polyamine solution are controlled to independently meet the above ranges, so that the acid-base resistant separation membrane prepared thereby has the pore size, surface Zeta potential and thickness required by the present invention, and can ensure that when the acid-base resistant separation membrane is used for magnesium-lithium separation in an acid / alkaline environment, it has a higher magnesium-lithium separation coefficient and water flux.
[0075] Furthermore, the concentration of the polyphenol is 0.0001wt%-0.1wt%.
[0076] Furthermore, the concentration of the first polyamine is 0.0001 wt%-0.1 wt%.
[0077] According to the present invention, the temperatures of the first contacting and the second contacting are independently 10-30°C.
[0078] In the present invention, when the temperature of the first contact and the second contact is controlled to meet the above range, it can ensure that the polyphenol and the first polyamine react fully, so that the prepared separation membrane has the required pore size and surface Zeta potential, and thus the acid-base resistant separation membrane has a higher magnesium-lithium separation efficiency and a higher retention rate.
[0079] According to the present invention, in a self-assembly reaction, the time of the first contact is 1-120 min.
[0080] According to the present invention, in a self-assembly reaction, the second contacting time is 1-120 min.
[0081] In the present invention, in a self-assembly reaction, the time of the first contact and the second contact is controlled to satisfy the above-mentioned range formula. On the basis of ensuring sufficient reaction, the density and thickness of the finally obtained acid-base resistant separation membrane can be controlled, so that the acid-base resistant separation membrane has higher water permeability and magnesium-lithium separation rate.
[0082] Furthermore, in a self-assembly reaction, the first contact time is 10-60 min.
[0083] Furthermore, in a self-assembly reaction, the second contact time is 10-60 min.
[0084] According to the present invention, the number of the self-assembly reaction is 1-10 times.
[0085] In the present invention, the inventors further discovered in their research that by following the above-mentioned method of preparing a modified layer on a poly(triazineamine-urea) layer of a material including a substrate layer, a base material layer, a porous support layer, and a poly(triazineamine-urea) layer, and repeating the following steps to complete multiple self-assemblies, it is possible to further ensure that the separation membrane has a higher surface Zeta potential and a smaller pore size, thereby further ensuring a higher magnesium-lithium separation efficiency.
[0086] Furthermore, the self-assembly reaction is performed 2-5 times.
[0087] According to the present invention, the conditions for preparing the modified layer include making the thickness of the modified layer in the separation membrane be 10-200 nm.
[0088] In the present invention, the separation membrane having the thickness of the modified layer as described above has a small pore size and a high Zeta potential. When used for magnesium-lithium separation in an acidic or alkaline environment, it can achieve both higher magnesium-lithium separation efficiency and water flux.
[0089] Furthermore, the conditions for preparing the modified layer include making the thickness of the modified layer in the separation membrane be 20-100 nm.
[0090] According to the present invention, the polyphenols in the polyphenol solution are selected from at least one of tannic acid, tea polyphenols, gallic acid, catechin, lignin, sodium lignin sulfonate, apple polyphenols, grape polyphenols, eriodictyol, naringenin, epicatechin, luteolin, apigenin, kaempferol, myricetin and genistein, preferably tannic acid and / or tea polyphenols.
[0091] According to the present invention, the first polyamine in the first polyamine solution is selected from at least one of polyethyleneimine, polyethyleneamine, polyethylenepolyamine, tetraethylenepentamine, triethylenetetramine, diethylenetriamine, polyethylenepolyamine, piperazine and N-aminoethylpiperazine, preferably at least one of polyethyleneimine, tetraethylenepentamine, triethylenetetramine and polyethylenepolyamine.
[0092] In the present invention, the method for preparing the porous support layer on the base layer can be a commonly used method in the art. However, preferably, the method for preparing the porous support layer comprises: coating a solution containing the porous support layer material on the base layer, performing phase inversion, and obtaining a material containing the base layer and the porous support layer.
[0093] According to the present invention, the phase conversion conditions include: soaking in water at 10-30° C. for 10-60 min.
[0094] In the present invention, when the method for preparing the porous support layer is adopted as described above, when immersed in water, the solvent in the solution containing the porous support layer material gradually leaves the porous support layer. Through this phase inversion method, it can be further ensured that a support layer with a porous structure is obtained.
[0095] According to the present invention, the thickness of the substrate layer is 30-150 μm, preferably 50-120 μm.
[0096] The thickness of the substrate layer does not change substantially before and after preparation.
[0097] According to the present invention, the material of the substrate layer is not particularly limited, and can be a material commonly used in the art that has a certain strength and is suitable for nanofiltration or reverse osmosis and can play a supporting role. However, preferably, the material of the substrate layer is selected from polyester non-woven fabric and / or polyethylene non-woven fabric.
[0098] According to the present invention, the conditions for preparing the porous supporting layer include making the thickness of the porous supporting layer in the separation membrane 10-100 μm, more preferably 30-60 μm.
[0099] It is understood that the thickness can be controlled by controlling the amount of coating, and since the thickness collapses after coating, the thickness set during coating will be slightly different from the thickness of the porous support layer in the separation membrane finally prepared. Generally, the thickness set during coating is about 40-60 μm higher than the porous support layer in the separation membrane to be obtained.
[0100] According to the present invention, the concentration of the solution containing the porous supporting layer material is 10 wt%-20 wt%.
[0101] According to the present invention, the porous support layer material is at least one selected from polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.
[0102] According to the present invention, the solvent in the solution containing the porous supporting layer material is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
[0103] In the present invention, there is no particular limitation on the method for preparing the solution containing the porous support layer material, and it can be prepared by conventional methods in the art. For example, the porous support layer material is first dissolved in a solvent and degassed (the degassed process can be performed at 20-40° C. for 10-180 min) to obtain a solution containing the porous support layer material.
[0104] In the present invention, after the porous support layer is prepared, the material may be washed, such as by washing with water for multiple times.
[0105] According to the present invention, the method for preparing the poly(triazineamine-urea) layer comprises: contacting the surface of the porous support layer of the material including the substrate layer and the porous support layer with an aqueous phase containing a second polyamine and an organic phase containing a triazine compound having at least two C-Cl bonds and a polyisocyanate in sequence, and then performing a heat treatment.
[0106] In the present invention, the poly(triazineamine-urea) layer is prepared by the above method, and has inert chemical groups, which can be suitable for acidic / alkaline environments; the surface modification layer can enhance the positive charge of the membrane surface, ensuring that the membrane has a high magnesium-lithium separation efficiency and water flux.
[0107] According to the present invention, the conditions for preparing the poly(triazineamine-urea) layer include making the thickness of the poly(triazineamine-urea) layer in the separation membrane 10-500 nm, more preferably 50-200 nm.
[0108] In the present invention, the poly(triazineamine-urea) layer is not only dense but also very thin, which further ensures a higher magnesium-lithium separation efficiency and water flux.
[0109] According to the present invention, the porous support layer contacts the aqueous phase containing the second polyamine for a period of 5-100 seconds.
[0110] According to the present invention, the porous support layer is in contact with the organic phase of the triazine compound containing at least two C-Cl bonds and the polyisocyanate for a period of 10-200 seconds.
[0111] In the present invention, the contact time between the porous support layer and the organic phase of the second polyamine, the triazine compound containing at least two C-Cl bonds and the polyisocyanate can allow the reaction to proceed fully, and the obtained poly(triazineamine-urea) layer has a high water flux and magnesium-lithium separation coefficient, and the reaction speed is fast and the process flow is simple.
[0112] Furthermore, the porous support layer contacts the aqueous phase containing the second polyamine for a period of 10-60 seconds.
[0113] Furthermore, the porous support layer contacts the organic phase of the triazine compound containing at least two C-Cl bonds and the polyisocyanate for 20-120 seconds.
[0114] According to the present invention, the amounts of the aqueous phase containing the second polyamine and the organic phase of the triazine compound containing at least two C-Cl bonds and the polyisocyanate are such that the mass ratio of the second polyamine to the triazine compound containing at least two C-Cl bonds and the polyisocyanate is 10-80:1-8:1.
[0115] The inventors of the present invention have found that when the mass ratio of the second polyamine, the triazine compound containing at least two C-Cl bonds and the polyisocyanate is controlled to meet the above ratio, the prepared poly(triazineamine-urea) layer has a suitable pore size, ensuring that the poly(triazineamine-urea) layer has excellent lithium chloride permeability while having a good retention rate for magnesium chloride.
[0116] At the same time, after the poly(triazineamine-urea) layer is modified with a polyphenol and a first polyamine, the pore size of the poly(triazineamine-urea) layer can be further reduced, and the surface Zeta potential can be further improved, and finally an acid-base resistant separation membrane having a specific pore size and surface Zeta potential as defined in the first aspect of the present invention is obtained. When the separation membrane is used for magnesium-lithium separation, the magnesium-lithium separation efficiency can be significantly improved.
[0117] Furthermore, the amounts of the aqueous phase containing the second polyamine and the organic phase containing the triazine compound containing at least two C-Cl bonds and the polyisocyanate are such that the mass ratio of the polyamine to the triazine compound containing at least two C-Cl bonds and the polyisocyanate is 20-70:1-5:1.
[0118] According to the present invention, the concentration of the aqueous phase containing the second polyamine is 0.2 wt %-10 wt %.
[0119] According to the present invention, the concentration of the organic phase of the triazine compound containing at least two C-Cl bonds is 0.05 wt%-2 wt%.
[0120] According to the present invention, the concentration of the organic phase containing polyisocyanate is 0.001 wt%-0.5 wt%.
[0121] In the present invention, the specific concentration of the second polyamine, the triazine compound containing at least two C-Cl bonds and the concentration of the polyisocyanate can make the reaction more complete, so that the finally obtained acid-base resistant separation membrane has a suitable density and thickness, thereby ensuring that the acid-base resistant separation membrane has a higher magnesium-lithium separation coefficient and water flux.
[0122] Furthermore, the concentration of the aqueous phase containing the second polyamine is 0.5wt%-5wt%.
[0123] Furthermore, the concentration of the organic phase of the triazine compound containing at least two C—Cl bonds is 0.1 wt%-1 wt%.
[0124] Furthermore, the concentration of the organic phase containing polyisocyanate is 0.01wt%-0.2wt%.
[0125] According to the present invention, the second polyamine is selected from at least one of triethylenetetramine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine, preferably polyethyleneimine and / or polyethylenepolyamine.
[0126] According to the present invention, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine, preferably cyanuric chloride.
[0127] According to the present invention, the polyisocyanate is selected from at least one of m-xylylene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate and 1,4-cyclohexyl diisocyanate, preferably 1,3-phenylene diisocyanate.
[0128] According to the present invention, the temperature of the heat treatment is 40-150° C.; the time of the heat treatment is 0.5-10 min.
[0129] In the present invention, the specific heat treatment conditions can make the reaction more complete, and make the finally obtained acid-base resistant separation membrane suitable for acid-base resistant environment, with a denser surface and both higher water flux and magnesium-lithium separation rate.
[0130] Furthermore, the temperature of the heat treatment is 50-120° C.; the time of the heat treatment is 1-5 min.
[0131] In the present invention, the ratio of the polyphenol solution to the membrane area of the poly(triazineamine-urea) layer of the material including the substrate layer, the porous support layer, and the poly(triazineamine-urea) layer is 5-30 mL / cm 2 .
[0132] In the present invention, the ratio of the first polyamine solution to the membrane area of the poly(triazineamine-urea) layer of the material including the substrate layer, the porous support layer, and the poly(triazineamine-urea) layer is 10-20 mL / cm 2 .
[0133] The third aspect of the present invention provides a separation membrane prepared by the above preparation method.
[0134] The fourth aspect of the present invention provides the application of the above acid-base resistant separation membrane in the field of water treatment.
[0135] The present invention will be described in detail below by way of examples, wherein:
[0136] In the following embodiments, when a material including a substrate layer, a porous support layer, and a poly(triazineamine-urea) layer is brought into contact with a solution in a cross-flow membrane pool, water is circulated into the membrane pool by a water pump in the cross-flow membrane pool, so that the polyphenol solution and the first polyamine solution in the membrane pool are in a flowing state.
[0137] The pore size of the acid-base resistant separation membrane is measured by the PEG solute transfer method, and the detailed steps are as follows:
[0138] (1) Test the retention rate of separation membrane for PEG with different molecular sizes;
[0139] (2) Linear fitting was performed between PEG size and retention rate in a logarithmic-probability coordinate system, and the PEG size corresponding to 50% retention rate was the average pore size of the separation membrane.
[0140] Surface Zeta potential of acid- and alkali-resistant separation membrane: The surface Zeta potential is measured in accordance with GB / T 37617-2019.
[0141] The content of N atoms in the modified layer of the acid- and alkali-resistant separation membrane is measured by X-ray photoelectron spectroscopy (XPS): obtained by Al-Kα X-ray irradiation on an ESCALAB250 X-ray photoelectron spectrometer.
[0142] Contents of structural units provided by polyphenols and structural units provided by the first polyamine in the acid-base resistant separation membrane:
[0143] The membrane including the substrate layer, the porous support layer, and the poly(triazineamine-urea) layer was dried in a vacuum oven at 60°C for 24 h, and the mass of the membrane was weighed as M. n , mg; the membrane is loaded into the membrane pool, and the feed tank is a certain concentration of polyphenol aqueous solution. After circulating for a certain period of time under certain conditions, the membrane is taken out, the surface of the membrane is rinsed with deionized water, and then dried at 60°C for 24 hours. The mass of the membrane is weighed as W n , mg; then the membrane is loaded into the membrane pool, and the feed tank is a first polyamine aqueous solution of a certain concentration. After circulating for a certain period of time under certain conditions, the membrane is taken out, the membrane surface is rinsed with deionized water, and then dried at 60°C for 24 hours. The mass of the membrane is weighed as N n , mg; the content of polyphenols on the membrane surface after each modification of the separation membrane P n And the content of polyamine T n They are calculated by the following formulas:
[0144]
[0145] When n is greater than 1, M n =N n-1 ; When n = 1, M n It is the mass of the original poly(triazineamine-urea) layer membrane;
[0146]
[0147] After the separation membrane is self-assembled, the total content of polyphenols on the surface is ΣPn, n≥1, and the total content of polyamines on the surface is ΣTn, n≥1;
[0148] Where n is the number of self-assembly times and S is the effective membrane area in cm 2 .
[0149] The conditions for contacting the membrane with the aqueous solution of polyphenol and the aqueous solution of the first polyamine correspond to the first pressure, second pressure, first contact temperature and time, and second contact temperature and time of the self-assembly process in the embodiment and comparative example, respectively.
[0150] Contact angle of acid- and alkali-resistant separation membrane: The surface contact angle of the composite membrane sample was tested using the sessile drop method using a DSA100 surface contact angle meter produced by KRUSS, Germany. Before the test, the sample was dried in a 60°C vacuum oven for 30 minutes to remove surface and internal moisture, and then the dried membrane was attached to a flat glass slide with double-sided tape. The volume of each water droplet during the test was 2 μL, and the water droplet was tested immediately after being dropped on the membrane surface for 3 seconds. The final contact angle was determined by taking the average value after multiple measurements.
[0151] Acid-base resistant separation membrane and thickness of each layer in the separation membrane: The thickness of the separation membrane, porous support layer, and poly(triazineamine-urea) layer is measured by a spiral micrometer and a scanning electron microscope, and the thickness of the modified layer is obtained by subtracting the thickness of the substrate layer, porous support layer, and poly(triazineamine-urea) layer from the thickness of the separation membrane. The thickness of the substrate layer is the thickness measured before coating the porous support layer material solution.
[0152] The test method of water flux of acid-base resistant separation membrane is as follows: the acid-base resistant separation membrane is loaded into the membrane pool, pre-pressed at 1.5MPa for 1h, and then the water permeation of the acid-base resistant separation membrane is measured under the conditions of pressure of 2MPa and temperature of 25°C within a certain period of time. The water flux is calculated by the following formula: J=Q / (A·t), wherein J is the water flux, Q is the water permeation (L), and A is the effective membrane area (m 2 ), t is time (h).
[0153] The test method of the desalination rate of the acid-base resistant separation membrane is as follows: the acid-base resistant separation membrane is placed in the membrane pool, pre-pressed at 1.5MPa for 1h, and then the concentration change of magnesium chloride in the original aqueous solution with an initial concentration of 2000ppm and the permeate is tested under the conditions of pressure 2MPa and temperature 25℃ within 1h. The desalination rate is calculated by the following formula: R = (C f -C p ) / C f ×100%, where R is the desalination rate, C f is the concentration of magnesium chloride in the stock solution, C p is the concentration of magnesium chloride in the permeate.
[0154] The test method of the magnesium-lithium separation coefficient of the acid-base resistant separation membrane is as follows: the acid-base resistant separation membrane is loaded into the membrane pool, the original aqueous solution is a mixture of 2000ppm magnesium chloride and 100ppm lithium chloride, and pre-pressed at 1.5MPa for 1h, and then the permeate is obtained under the conditions of pressure 2MPa and temperature 25°C. The mass concentrations of magnesium ions and lithium ions in the original solution and the permeate are measured by ion chromatography, and the lithium-magnesium separation coefficient is calculated by the following formula:
[0155]
[0156] Where S is the lithium-magnesium separation coefficient, C Mg,f and C Li,f are the mass concentrations of magnesium ions and lithium ions in the raw water (measured by ion chromatography); C Mg,p and C Li,p are the mass concentrations of magnesium ions and lithium ions in the permeate, respectively (measured by ion chromatography).
[0157] Testing method for acid resistance of acid-base resistant separation membrane: soak the membrane of the acid-base resistant separation membrane in a 5wt% HCl solution for 7 days, and test the changes in magnesium-lithium separation coefficient and water flux of the acid-base resistant separation membrane.
[0158] Branched polyethyleneimine (weight-average molecular weight of 25,000 g / mol), polyethylene polyamine, tetraethylene pentamine, cyanuric chloride, 2,4-dichloro-6-phenyl-1,3,5-triazine, 1,3-phenylene diisocyanate, toluene-2,4-diisocyanate, tannic acid, gallic acid, tea polyphenols, etc. were purchased from J&K Technology Co., Ltd., and other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0159] The porous support layer is prepared by a phase inversion method, and the specific steps are as follows:
[0160] Polysulfone (number average molecular weight of 80000 g / mol) was dissolved in N,N-dimethylformamide to obtain a polysulfone solution with a concentration of 18 wt%, and degassed at 25°C for 120 min. The polysulfone solution was then coated on a polyester non-woven fabric (substrate layer) with a thickness of 75 μm using a scraper, and then immersed in water at a temperature of 25°C for 60 min, so that the polysulfone layer on the surface of the polyester non-woven fabric was transformed into a porous membrane through phase conversion, and finally washed with water three times to obtain a material including a substrate layer and a porous support layer (porous support layer is 40 μm) with a total thickness of 115 μm and an area of 400 cm 2 .
[0161] Example 1
[0162] (1) The surface of the porous support layer of the material including the substrate layer and the porous support layer is contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine, and the liquid is drained after contacting for 60 seconds at 25°C; then, the upper surface of the support layer is contacted with 30 mL of an Isopar E solution containing 0.15 wt% cyanuric chloride and 0.05 wt% 1,3-phenylene diisocyanate, and the liquid is drained after contacting for 60 seconds at 25°C; then, the membrane is placed in an oven and heated at 70°C for 3 minutes.
[0163] (2) The heat-treated product is loaded into a cross-flow test system, so that one side of the poly(triazineamine-urea) layer of the material is first contacted with a 0.001wt% tannic acid aqueous solution in the cross-flow membrane pool, the volume of the tannic acid aqueous solution is 5L, and the test system is operated at 2MPa and 25°C for 30min, then the liquid is drained and the test system is repeatedly rinsed with deionized water to clean the residual tannic acid in the system; 5L of a 0.004wt% polyethyleneimine aqueous solution is added to the cross-flow test system for second contact, and the test system is operated at 2MPa and 25°C for 30min, then the liquid is drained and the test system is repeatedly rinsed with deionized water to clean the residual polyethyleneimine in the system; thereby completing a self-assembly process, repeating the above operation to perform another self-assembly process, and obtaining an acid-base resistant separation membrane N1;
[0164] Figure 1 The characteristic peak at 407 eV corresponds to the structural unit shown in Formula I, which is the signal peak generated by the π-π* electronic conjugation formed by benzene ring-nitrogen atom-benzene ring. One nitrogen atom in this structural unit undergoes a cross-linking reaction with two benzene rings, which further reduces the pore size of the separation membrane, improves the density of the separation membrane, and enables the separation membrane to have a high magnesium-lithium separation coefficient.
[0165] Example 2
[0166] The method of Example 1 is followed, except that in step (2), 5 L of 0.01 wt % tea polyphenols are added instead of tannic acid, and 5 L of 0.04 wt % polyethyleneimine aqueous solution is added instead of 0.004 wt % polyethyleneimine aqueous solution to obtain acid-base resistant separation membrane N2.
[0167] Example 3
[0168] The method of Example 1 is followed, except that in step (2), 5 L of 0.1 wt % gallic acid is added instead of tannic acid, and 5 L of 0.04 wt % polyethyleneimine aqueous solution is added instead of 0.004 wt % polyethyleneimine aqueous solution to obtain acid-base resistant separation membrane N3.
[0169] Example 4
[0170] The method of Example 1 was followed, except that in step (1), 30 mL of 0.15 wt % Isopar E solution of 2,4-dichloro-6-phenyl-1,3,5-triazine and 0.05 wt % toluene-2,4-diisocyanate was added instead of 30 mL of 0.15 wt % Isopar E solution of cyanuric chloride and 0.05 wt % 1,3-phenylene diisocyanate to obtain acid-base resistant separation membrane N4.
[0171] Example 5
[0172] The method of Example 1 was used for implementation, except that in step (1), the surface of the porous support layer of the material including the substrate layer and the porous support layer was contacted with 60 mL of an aqueous solution containing 2 wt% polyethyleneimine, and the liquid was discharged after contacting at 25°C for 60 s; then, the upper surface of the support layer was contacted with 30 mL of an Isopar E solution containing 0.3 wt% of cyanuric chloride and 0.05 wt% of 1,3-phenylene diisocyanate, and the liquid was discharged after contacting at 25°C for 60 s; then, the membrane was placed in an oven and heated at 70°C for 3 min; and step (2) was implemented according to the method of Example 1 to obtain an acid-base resistant separation membrane N5.
[0173] Example 6
[0174] The method of Example 1 is followed, except that in step (2), polyethyleneimine is replaced by polyethylene polyamine during the self-assembly process to obtain an acid-base resistant separation membrane N6.
[0175] Example 7
[0176] The method of Example 1 is followed, except that in step (2), polyethyleneimine is replaced by tetraethylenepentamine during the self-assembly process to obtain an acid-base resistant separation membrane N7.
[0177] Example 8
[0178] The method of Example 1 was followed, except that the number of self-assembly was one, and an acid-base resistant separation membrane N8 was obtained.
[0179] Example 9
[0180] The method of Example 1 was followed, except that the number of self-assembly was 5 times, to obtain an acid-base resistant separation membrane N9.
[0181] Example 10
[0182] The method of Example 1 is used, except that in step (1), triethylenetetramine is used instead of polyethyleneimine to obtain an acid-base resistant separation membrane N10.
[0183] Embodiment 11
[0184] The method of Example 1 was followed, except that the first pressure was 1.5 MPa and the second pressure was 1.5 MPa, to obtain an acid- and alkali-resistant separation membrane N11.
[0185] Example 12
[0186] The method of Example 1 was followed, except that the first pressure was 1.5 MPa and the second pressure was 3 MPa, to obtain an acid- and alkali-resistant separation membrane N12.
[0187] Embodiment 13
[0188] The method of Example 1 was followed, except that the first pressure was 1 MPa and the second pressure was 1.5 MPa, to obtain an acid- and alkali-resistant separation membrane N13.
[0189] Comparative Example 1
[0190] The method of Example 1 was followed, except that no polyphenol and the first polyamine were added, to obtain an acid-base resistant separation membrane D1.
[0191] Comparative Example 2
[0192] The method of Example 1 was followed, except that the first polyamine was not added, to obtain an acid-base resistant separation membrane D2.
[0193] Comparative Example 3
[0194] The method of Example 1 was followed, except that immersion was used instead of the first contact and immersion was used instead of the second contact, to obtain an acid-base resistant separation membrane D3.
[0195] The results of the structure-related performance tests on the acid- and alkali-resistant separation membranes are shown in Tables 1 and 2.
[0196] Table 1
[0197]
[0198] Table 2
[0199]
[0200] The water flux of the acid-base resistant separation membrane prepared in the embodiment and the comparative example, the desalination rate of magnesium chloride and lithium chloride, and the magnesium-lithium separation coefficient of the membrane were tested; after the acid-base resistant separation membrane of the embodiment and the comparative example was treated with acid, the magnesium-lithium separation coefficient and water flux of the acid-base resistant separation membrane were tested, and the results are shown in Table 3.
[0201] Table 3
[0202]
[0203]
[0204] It can be seen from the results of Table 1, Table 2 and Table 3 that, by comparing the embodiment with the comparative example, the Zeta potential in the embodiment is higher, and when it is used for magnesium-lithium separation, it can allow monovalent lithium ions to pass as much as possible while rejecting divalent magnesium ions, so that the separation membrane has a higher magnesium-lithium separation coefficient. From the data of "5wt% HCl treatment for 7 days" in Table 3, it can be seen that the separation membrane after acid treatment still has a higher separation coefficient. The separation membrane of the present invention can be used for magnesium-lithium separation under acidic conditions;
[0205] Comparison of Examples 1-3 shows that the types and amounts of the polyphenol and the first polyamine act synergistically to jointly affect the water flux and magnesium-lithium separation coefficient of the prepared acid-base resistant separation membrane;
[0206] Compared with Example 1 and Example 8 and Example 9, the assembly meeting the technical solution of the present invention can obtain a more excellent water flux and magnesium-lithium separation coefficient;
[0207] In Example 10, compared with the aqueous phase using polyethyleneimine rich in amino groups in its structure, when small molecule amine monomers are selected, the pore size of the poly(triazineamine-urea) separation layer obtained by interfacial polymerization is larger, and the separation membrane obtained after surface self-assembly has a lower retention rate for magnesium chloride, so the magnesium-lithium separation coefficient is also lower.
[0208] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An acid-base resistant separation membrane, characterized in that: The acid-base resistant separation membrane comprises a substrate layer, a porous support layer, a poly(triazineamine-urea) layer and a modification layer in sequence; The cross-linked polymer forming the modified layer includes structural units provided by polyphenols and structural units provided by the first polyamine, and at least part of the structural units provided by the polyphenols are also connected to the poly(triazineamine-urea) layer via the ortho position of the phenolic hydroxyl group; The pore size of the separation membrane is 0.1-0.5 nm, and the surface Zeta potential of the acid-base resistant separation membrane is 0-30 mV.
2. The acid- and alkali-resistant separation membrane according to claim 1, wherein The pore size of the separation membrane is 0.15-0.3 nm, and the surface Zeta potential of the separation membrane is 5 mV to 20 mV.
3. The acid-base resistant separation membrane according to claim 1 or 2, wherein The modified layer comprises a structural unit shown in Formula I; 4. The acid-base resistant separation membrane according to any one of claims 1 to 3, wherein: The content of the structural units provided by the polyphenol on the membrane surface is 2×10 -3 -5×10 -2 mg / cm 2 , preferably 1×10 -2 -3×10 -2 mg / cm 2 The content of the structural unit provided by the first polyamine on the membrane surface is 1×10 -3 -2.5×10 -2 mg / cm 2 , preferably 5×10 -3 -2×10 -2 mg / cm 2 .
5. The acid-base resistant separation membrane according to any one of claims 1 to 4, wherein: The content of N atoms in the modified layer is 10-20 at.%, preferably 14-18 at.%.
6. The acid-base resistant separation membrane according to any one of claims 1 to 5, wherein: The contact angle of the separation membrane is 20-60°, preferably 20-50°.
7. The acid-base resistant separation membrane according to any one of claims 1 to 6, wherein: The thickness of the separation membrane is 100-200 μm; Preferably, the thickness of the substrate layer is 30-150 μm, preferably 50-120 μm; Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; Preferably, the thickness of the poly(triazineamine-urea) layer is 10-500 nm, preferably 50-200 nm; Preferably, the thickness of the modified layer is 10-200 nm, preferably 10-60 nm.
8. The acid-base resistant separation membrane according to any one of claims 1 to 7, wherein: The material of the substrate layer is selected from polyester non-woven fabric and / or polyethylene non-woven fabric; Preferably, the material of the porous support layer is at least one selected from polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.
9. The acid-base resistant separation membrane according to any one of claims 1 to 7, wherein: The poly(triazineamine-urea) layer is synthesized from a second polyamine, a triazine compound containing at least two C-Cl bonds, and a polyisocyanate; Preferably, the second polyamine is selected from at least one of triethylenetetramine, tetraethylenepentamine, polyethylene polyamine, polyethylene imine and polyetheramine, preferably polyethylene imine and / or polyethylene polyamine; Preferably, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine, preferably cyanuric chloride; Preferably, the polyisocyanate is selected from at least one of meta-xylylene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate and 1,4-cyclohexyl diisocyanate, preferably 1,3-phenylene diisocyanate.
10. The acid-base resistant separation membrane according to any one of claims 1 to 9, wherein: The modified layer is obtained by self-assembly reaction of a polyphenol and a first polyamine on a poly(triazineamine-urea) layer; Preferably, the polyphenol is selected from at least one of tannic acid, tea polyphenol, lignin, sodium lignin sulfonate, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, gallic acid, protocatechuic acid, apigenin, kaempferol, myricetin and genistein, preferably tannic acid and / or tea polyphenol; Preferably, the first polyamine is selected from at least one of polyethyleneimine, polyethyleneamine, polyethylenepolyamine, tetraethylenepentamine, triethylenetetramine, diethylenetriamine, polyethylenepolyamine, piperazine and N-aminoethylpiperazine, preferably at least one of polyethyleneimine, tetraethylenepentamine, triethylenetetramine and polyethylenepolyamine.
11. A method for preparing an acid- and alkali-resistant separation membrane, characterized in that: The preparation method comprises the following steps: sequentially preparing a porous support layer, a poly(triazineamine-urea) layer and a modification layer on a substrate layer; Among them, the method for preparing the modified layer includes: under a first pressure, while the polyphenol solution is kept flowing, a poly(triazineamine-urea) layer side of a material including a substrate layer, a porous support layer, and a poly(triazineamine-urea) layer is brought into first contact with a polyphenol solution; under a second pressure, while the first polyamine solution is kept flowing, a poly(triazineamine-urea) layer side of the material is brought into second contact with a first polyamine solution to complete a self-assembly reaction.
12. The preparation method according to claim 11, wherein The first pressure and the second pressure are each independently 1-3 MPa, preferably 1.5-2 MPa; Preferably, the amounts of the polyphenol solution and the first polyamine solution are such that the mass ratio of the polyphenol to the first polyamine is 0.1-10:1, preferably 0.25-6:1; Preferably, the concentration of the polyphenol is 0.00001wt%-1wt%, preferably 0.0001wt%-0.1wt%; Preferably, the concentration of the first polyamine is 0.00001 wt%-1 wt%, preferably 0.0001 wt%-0.1 wt%.
13. The preparation method according to claim 11 or 12, wherein: The temperatures of the first contact and the second contact are each independently 10-30°C; Preferably, in one self-assembly reaction, the first contacting time is 1-120 min, preferably 10-60 min; Preferably, in one self-assembly reaction, the second contacting time is 1-120 min, more preferably 10-60 min; Preferably, the number of self-assembly reactions is 1-10 times, more preferably 2-5 times; Preferably, the conditions for preparing the modified layer include making the thickness of the modified layer in the separation membrane 10-200 nm, preferably 20-100 nm.
14. The preparation method according to any one of claims 11 to 13, wherein: The polyphenol in the polyphenol solution is at least one selected from tannic acid, tea polyphenol, gallic acid, catechin, lignin, sodium lignin sulfonate, apple polyphenol, grape polyphenol, eriodictyol, naringenin, epicatechin, luteolin, apigenin, kaempferol, myricetin and genistein, preferably tannic acid and / or tea polyphenol; Preferably, the first polyamine in the first polyamine solution is selected from at least one of polyethyleneimine, polyethyleneamine, polyethylenepolyamine, tetraethylenepentamine, triethylenetetramine, diethylenetriamine, polyethylenepolyamine, piperazine and N-aminoethylpiperazine, preferably at least one of polyethyleneimine, tetraethylenepentamine, triethylenetetramine and polyethylenepolyamine.
15. The preparation method according to any one of claims 11 to 14, wherein: The method for preparing the porous support layer comprises: coating a solution containing a porous support layer material on the substrate layer, and performing phase inversion to obtain a material containing a substrate layer and a porous support layer; Preferably, the phase inversion conditions include: soaking in water at 10-30°C for 10-60 min; Preferably, the thickness of the substrate layer is 30-150 μm, preferably 50-120 μm; Preferably, the material of the substrate layer is selected from polyester non-woven fabric and / or polyethylene non-woven fabric; Preferably, the conditions for preparing the porous support layer include making the thickness of the porous support layer in the separation membrane 10-100 μm, more preferably 30-60 μm; Preferably, the concentration of the solution containing the porous support layer material is 10wt%-20wt%; Preferably, the porous support layer material is selected from at least one of polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone; Preferably, the solvent in the solution containing the porous supporting layer material is at least one selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
16. The preparation method according to any one of claims 11 to 15, wherein: The method for preparing the poly(triazineamine-urea) layer comprises: contacting the surface of the porous support layer of the material including the substrate layer and the porous support layer with an aqueous phase containing a second polyamine and an organic phase containing a triazine compound having at least two C-Cl bonds and a polyisocyanate in sequence, and then heat treating; Preferably, the conditions for preparing the poly(triazineamine-urea) layer include making the thickness of the poly(triazineamine-urea) layer in the separation membrane 10-500 nm, more preferably 50-200 nm; Preferably, the time for the surface of the porous support layer to contact the aqueous phase containing the second polyamine is 5-100 s, more preferably 10-60 s; Preferably, the time for the surface of the porous support layer to contact the organic phase of the triazine compound containing at least two C-Cl bonds and the polyisocyanate is 10-200 s, more preferably 20-120 s; Preferably, the amount of the aqueous phase containing the second polyamine and the organic phase of the triazine compound containing at least two C-Cl bonds and the polyisocyanate is such that the mass ratio of the second polyamine to the triazine compound containing at least two C-Cl bonds and the polyisocyanate is 10-80:1-8:1, preferably 20-70:1-5:1; Preferably, the concentration of the aqueous phase containing the second polyamine is 0.2wt%-10wt%, more preferably 0.5wt%-5wt%; Preferably, the concentration of the organic phase of the triazine compound containing at least two C-Cl bonds is 0.05wt%-2wt%, more preferably 0.1wt%-1wt%; Preferably, the concentration of the polyisocyanate-containing organic phase is 0.001wt%-0.5wt%, more preferably 0.01wt%-0.2wt%; Preferably, the second polyamine is selected from at least one of triethylenetetramine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine, preferably polyethyleneimine and / or polyethylenepolyamine; Preferably, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine, preferably cyanuric chloride; Preferably, the polyisocyanate is selected from at least one of meta-xylylene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate and 1,4-cyclohexyl diisocyanate, preferably 1,3-phenylene diisocyanate; Preferably, the temperature of the heat treatment is 40-150°C, more preferably 50-120°C; the time of the heat treatment is 0.5-10 min, more preferably 1-5 min.
17. An acid- and alkali-resistant separation membrane prepared by the method according to any one of claims 11 to 16.
18. Use of the acid-base resistant separation membrane described in any one of claims 1 to 10 and claim 17 in magnesium-lithium separation.
Citation Information
Patent Citations
Nano-filtration membrane, preparation method and applications of thereof
CN109692584A
Preparation method of polytriazine alkali-resistant composite nanofiltration membrane
CN114130220A
Copolymer membrane and enzymatic self-assembly synthesis method and application thereof on gas-liquid interface
CN115612699A
Composite membranes useful for the separation of organic compounds of low molecular weight from aqueous inorganic salts containing solutions
US4767645A